The Impact of COVID-19 on the HIV Cascade of Care in Botswana – An Interrupted Time Series. - Sehurutshi, Alice; Farooqui, Habib; Chivese, Tawanda (AIDS & Behavior, 2024)
Globally, Botswana has one of the highest burdens of HIV. This study estimated the impact of the COVID-19 pandemic on the HIV cascade of care in Sub-Saharan Africa. We conducted an interrupted time series analysis on national-level data to estimate the effect of COVID-19 on the numbers of HIV tests, positive HIV tests and ART initiations from April 2019 until March 2021. In multivariable Poisson interrupted time series regression, the COVID-19 lockdown was associated with a 27% decrease in the monthly numbers of HIV tests (IRR 0.73, 95%CI 0.72–0.73), a 25% decrease in HIV positive tests (IRR 0.75, 95%CI 0.71–0.79), and a 43% reduction in ART initiations (IRR 0.57, 95%CI 0.55–0.60). The impact of the pandemic on all three outcomes was worse in males and those aged ≥ 50 years. In conclusion, COVID-19 had a strong negative impact on HIV screening, diagnosis and ART initiation in Botswana.